Implementasi dan Peran Dinas Koperasi UKM Kabupaten Karawang Dalam Pengembangan Koperasi Modern dan UMKM Berdasarkan Peraturan Daerah No. 7 Tahun 2022 Tentang Pelindungan dan Pemberdayaan Koperasi dan Usaha Mikro - Karina, Karina Luana Pramesti; taun, Taun (Jurnal Panorama Hukum, 2022)
The purpose of the study is to determine and analyse the role of the Karawang Regency SME Cooperative Office in empowering and protecting cooperatives and MSMEs as well as having obstacles and solutions in the implementation of Karawang Regency Regional Regulation No. 7 of 2022 concerning Protection and Empowerment of Cooperatives and Micro Enterprises. The results of the study found that the Karawang Regency local government made the regulation of Regional Regulation No. 7 of 2022 considering the inauguration of the Job Creation Law as described in PP No.7 of 2021 for cooperatives and MSMEs. The research method is empirical juridical, in substance it aims to develop MSME cooperatives in establishing cooperatives, making cooperatives carry out modernisation and digitalisation (training), and MSMEs have higher quality. Some examples of empowerment and protection provided such as ease in arranging business licences, business capital assistance, provision of promotional places for MSEs in public infrastructure (outlets) Dinkop Karawang, and provision of legal aid services and legal assistance. Some of the difficulties that arise in the development of MSMEs and cooperatives include the low quality of cooperatives and the lack of MSME operations that are in accordance with relevant legal regulations.